Educational Robotics in the Makers Era - Alimisis, Dimitris; Moro, Michele; Menegatti, Emanuele (Advances in Intelligent Systems and Computing, 2017)
This book includes papers presented at the International Conference "Educational Robotics 2016 (EDUROBOTICS)", Athens, November 25, 2016. The papers build on constructivist and constructionist pedagogy and cover a variety of topics, including teacher education, design of educational robotics activities, didactical models, assessment methods, theater robotics, programming & making electronics with Snap4Arduino, the Duckietown project, robotics driven by tangible programming, Lego Mindstorms combined with App Inventor, the Orbital Education Platform, Anthropomorphic Robots and Human Meaning Makers in Education, and more. It provides researchers interested in educational robotics with the latest advances in the field with a focus on science, technology, engineering, arts and mathematics (STEAM) education. At the same time it offers teachers and educators from primary to secondary and tertiary education insights into how educational robotics can trigger the development of technological interest and 21st century skills in STEAM education (creative thinking, team working, problem solving).